品种和产地对核桃油脂肪酸组成及含量的影响 "Effects of varieties and producing areas on fatty acid composition and content of walnut oil" - 时杨妮1，李鑫鑫1，马兆成1,2 SHI Yangni1, LI Xinxin1, MA Zhaocheng1,2 (Zhongguo youzhi)
旨在为核桃品种选育和核桃油产品开发提供理论依据，探究不同品种和产地核桃油中脂肪酸组成及含量差异。以51个品种核桃、7个产地的香玲核桃和5个产地的清香核桃为研究对象，利用气相色谱-质谱联用仪测定其油脂的脂肪酸组成及含量，并进行相关性分析、主成分分析与聚类分析。结果表明：51个品种核桃油中含13种脂肪酸，含量较高的依次是亚油酸、油酸、α-亚麻酸、棕榈酸、硬脂酸，这5种脂肪酸总含量约占总脂肪酸含量的99%，不饱和脂肪酸含量高达90%左右；51个品种核桃油中脂肪酸含量差异显著，5种主要脂肪酸中油酸的变异系数最高，为23.14%，α-亚麻酸变异系数次之，为14.86%，亚油酸的变异系数为7.24%；相关性分析发现，硬脂酸含量与棕榈酸含量呈极显著负相关，α-亚麻酸含量与油酸含量呈极显著负相关，与亚油酸含量呈极显著正相关，亚油酸含量与油酸含量呈极显著负相关；通过主成分分析和聚类分析将51个核桃品种分为3类，第1类为中油酸、中亚油酸组，第2类为低油酸、高亚油酸组，第3类为高油酸、低亚油酸组；不同产地核桃油的脂肪酸组成与不同品种核桃油一致，同一品种不同产地核桃油之间脂肪酸含量差异较小，经主成分分析和聚类分析发现甘肃华亭清香核桃单独为一类，其他产地的清香核桃为一类，不同产地的香玲核桃为一类。综上，核桃油脂肪酸含量受产地影响较小，主要是由品种决定，具有一定的遗传稳定性。 In order to provide a theoretical basis for the breeding of walnut varieties and the development of walnut oil products, the differences in fatty acid composition and content of walnut oil from different varieties and producing areas were explored. A total of 51 varieties of walnuts, Xiangling walnuts from 7 producing areas and Qingxiang walnuts from 5 producing areas were used as research objects，the composition and content of fatty acid in walnut oil were determined by gas chromatography-mass spectrometry (GC-MS), and correlation analysis, principal component analysis (PCA) and cluster analysis were carried out.The results showed that 51 varieties of walnut oils contained 13 kinds of fatty acids, and the total contents of linoleic acid, oleic acid, α-linolenic acid, palmitic acid and stearic acid were higher, and they accounted for about 99% of the total fatty acid content, the content of unsaturated fatty acid in walnut oil was as high as about 90%. The content of fatty acid in 51 varieties of walnut oil was significantly different. The coefficient of variation of oleic acid was the highest (23.14%) in the five main fatty acid, the coefficient of variation of α-linolenic acid was the second (14.86%), and the coefficient of variation of linoleic acid was 7.24%. Correlation analysis showed that there was a highly significant negative correlation between stearic acid content and palmitic acid content. The content of α-linolenic acid was highly significantly negatively correlated with the content of oleic acid, and it was highly significantly positively correlated with the content of linoleic acid. Linoleic acid content was highly significantly negatively correlated with oleic acid content.Through cluster analysis and PCA, 51 walnut varieties were divided into three categories. The first category was medium oleic acid and medium linoleic acid group, the second category was low oleic acid and high linoleic acid group, and the third category was high oleic acid and low linoleic acid group. The composition of fatty acid in walnut oil from different producing areas was consistent with that of different varieties of walnut oil. The difference of fatty acid content of walnut oil between different producing areas of the same variety was small. Through cluster analysis and PCA, it was found that the Qingxiang walnut in Huating, Gansu Province was a separate category, the Qingxiang walnuts in other producing areas were clustered into one category, and the Xiangling walnuts in different producing areas were clustered into one category. In conclusion, the fatty acid content is less affected by the producing area, mainly determined by the variety, amd it has certain genetic stability.